TAX SOCIALIZATION AS A MODERATING VARIABLE OF NIK-NPWP IMPLEMENTATION ON TAXPAYER COMPLIANCE - Ni Ketut Arista Ameliasari; Kadek Wulandari Laksmi P; Ketut Tanti Kustina; Putu Putri Prawitasari (Jurnal Ilmu Akuntansi, 2025)
This study aims to influence the effect of NIK-NPWP implementation on individual taxpayer compliance with tax socialization as a moderating variable. The research gap arising from inconsistent findings in previous studies regarding effectiveness of the NIK-NPWP policy in improving taxpayer compliance. The research method used a quantitative approach using purposive sampling. The sample consists of individual non-employee taxpayers registered at the KPP Pratama Badung Selatan who have completed NIK-NPWP integration and filed their 2024 annual tax return. Data collected through the distribution of questionnaires and analyzed using Moderated Regression Analysis (MRA) with SPSS. The results of study reveal that the implementation of NIK-NPWP has a positive and significant effect on taxpayer compliance. Furthermore, tax socialization strengthens the relationship between NIK-NPWP implementation on taxpayer compliance. The findings indicating that effective tax socialization by tax authority enhance the impact of NIK-NPWP implementation. The study concludes that tax socialization plays a crucial role in amplifying the effectiveness of NIK-NPWP implementation. These results provide valuable insights for the Directorate General of Taxes to improve communication and educational strategies in promoting tax reformations while also enriching behavioral tax compliance theory in the context of administrative modernization.